The Effect of Islamic Leadership and Islamic Compensation on Employee Performance with Employee's Commitment as Moderation in Islamic Boarding School's Businesses - Ari Prasetyo; Mochammad Soleh; Nurul Hidayati (al-Uqud : Journal of Islamic Economics, 2021)
This research aims to analyze the influence of Islamic leadership, Islamic compensation on employee performance with employee commitment as a moderator in Islamic boarding school cooperatives in Surabaya. This research is a research explanation research. The population in this study are employees of the boarding school's cooperative business unit. The sample is some employees in the Surabaya Islamic boarding school cooperative, which amounted to 139 respondents. The data collection technique used in this study was a survey using a questionnaire. The independent variable used in the results of this study is given an X notation, namely: Islamic leadership and Islamic compensation. The moderating variables are organizational commitment (Z). The dependent variable of employee performance (Y). Measurements in the questionnaire using a five-point Likert scale. The analysis technique used in this research is Structural Equation Modeling with the Smart PLS (Partial Least Square) program. The result shows that Islamic leadership significantly affects employee performance, while Islamic compensation does not. This research proves that commitment as a moderating factor for Islamic leadership and Islamic compensation in Islamic boarding schools is not optimal. In Islamic leadership, commitment weakens the influence of Islamic leadership on employee performance and strengthens compensation on employee performance.